Can a Novel Clinical Risk Score Improve Pneumonia Prediction in Acute Stroke Care? A UK Multicenter Cohort Study. Issue 1 (13th January 2015) - Smith, Craig J.; Bray, Benjamin D.; Hoffman, Alex; Meisel, Andreas; Heuschmann, Peter U.; Wolfe, Charles D. A.; Tyrrell, Pippa J.; Rudd, Anthony G.; ,
Abstract : Background: Pneumonia frequently complicates stroke and has a major impact on outcome. We derived and internally validated a simple clinical risk score for predicting stroke‐associated pneumonia (SAP), and compared the performance with an existing score (A 2 DS 2 ). Methods and Results: We extracted data for patients with ischemic stroke or intracerebral hemorrhage from the Sentinel Stroke National Audit Programme multicenter UK registry. The data were randomly allocated into derivation (n=11 551) and validation (n=11 648) samples. A multivariable logistic regression model was fitted to the derivation data to predict SAP in the first 7 days of admission. The characteristics of the score were evaluated using receiver operating characteristics (discrimination) and by plotting predicted versus observed SAP frequency in deciles of risk (calibration). Prevalence of SAP was 6.7% overall. The final 22‐point score ( ISAN : prestroke I ndependence [modified Rankin scale], S ex, A ge, N ational Institutes of Health Stroke Scale) exhibited good discrimination in the ischemic stroke derivation (C‐statistic 0.79; 95% CI 0.77 to 0.81) and validation (C‐statistic 0.78; 95% CI 0.76 to 0.80) samples. It was well calibrated in ischemic stroke and was further classified into meaningful risk groups (low 0 to 5, medium 6 to 10, high 11 to 14, and very high ≥15) associated with SAP frequencies of 1.6%, 4.9%, 12.6%, and 26.4%, respectively, in the validation sample. Discrimination for both scores was similar, although they performed less well in the intracerebral hemorrhage patients with an apparent ceiling effect. Conclusions: The ISAN score is a simple tool for predicting SAP in clinical practice. External validation is required in ischemic and hemorrhagic stroke cohorts.